PENINGKATAN AKTIVITAS BELAJAR SISWA DALAM MATA PELAJARAN PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DI KELAS I SDN 45 PULAU KARAM - Erlina Erlina (STKIP Pesisir Selatan, 2018)
ABSTRACTBased on the learning activities of Class I students of SDN 45 Pulau Karam in PKN subjects it was found that student learning activities in PKN subjects were still very low. The purpose of this study is to describe and obtain information about Increasing Student Learning Activities in PKN subjects through cooperative learning models Think Talk Write in Class I SDN 45 Pulau Karam, West Pasaman District. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 30 Class I students at SDN 45 Karam Island. The research data was collected using an observation sheet. Data were analyzed using percentages. Based on the results of the research and discussion presented in the previous chapter, it can be concluded that it can be concluded that the type of cooperative learning learning model Think Talk Write can improve student learning activities in PKN subjects at SDN 45 Karam Island. Student learning activities in the first cycle were 71.73 (sufficient) to increase to 82.23 (good) with an increase of 10.5.